Requirements of performance development for educational offices Yemen Republic in the light of continuous level improvement methodology kaizen - Ashaibah, Murad Ali Abdullah; Al-Najjar, Abdullah Ali Saleh (Journal of Educational and Psychological Sciences, 2022)
The aim of the research is to identify the degree of availability of requirements for developing the performance of leaders of education offices in the Republic of Yemen in the light of the kaizen continuous improvement methodology, and to find out whether there are statistically significant differences at the level (0.05) between the average responses of the research sample members due to Research variables: (gender, scientific specialization, job title). The research relied on the analytical descriptive approach. The researcher used a questionnaire consisting of (16) item variable, which was applied to a sample of (285) leader. The research found a set of results, the most important of which are: The degree of availability of requirements for developing the performance of leaders of education offices in the Republic of Yemen in the light of the kaizen continuous improvement methodology came with a “weak” estimate, with a mean (2.13), as the results showed. There are statistically significant differences attributable to the gender variable, in favor of males, and the results show that there are statistically significant differences attributable to the variable of scientific specialization in favor of the non-educational, as well as the presence of statistically significant differences due to the job title variable, in favor of general managers, and in light of the results recommended The research made a number of recommendations, the most important of which are: Designing training programs to develop the performance of educational leaders in practicing kaizen continuous improvement and transforming them into creative leaders.